2016
DOI: 10.1021/acsami.6b02137
|View full text |Cite
|
Sign up to set email alerts
|

All-Nonvacuum-Processed CIGS Solar Cells Using Scalable Ag NWs/AZO-Based Transparent Electrodes

Abstract: With record cell efficiency of 21.7%, CIGS solar cells have demonstrated to be a very promising photovoltaic (PV) technology. However, their market penetration has been limited due to the inherent high cost of the cells. In this work, to lower the cost of CIGS solar cells, all nonvacuum-processed CIGS solar cells were designed and developed. CIGS absorber was prepared by the annealing of electrodeposited metallic layers in a chalcogen atmosphere. Nonvacuum-deposited Ag nanowires (NWs)/AZO transparent electrode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…The AgNWs-only film had floating values on for Rs from 12.7 to 18.0 Ω/sq because the rough surface of the electrode produces random connection with the four-point probe. The sample with 3, 6, and 9 nm AZO had 12.0 ± 1.5, 8.66 ± 0.4, and 9.1 ± 1.4 Ω/sq, respectively [ 24 ]. For organic device electrodes, the optical transmittance is an important parameter, because it directly affects the light output coupling.…”
Section: Resultsmentioning
confidence: 99%
“…The AgNWs-only film had floating values on for Rs from 12.7 to 18.0 Ω/sq because the rough surface of the electrode produces random connection with the four-point probe. The sample with 3, 6, and 9 nm AZO had 12.0 ± 1.5, 8.66 ± 0.4, and 9.1 ± 1.4 Ω/sq, respectively [ 24 ]. For organic device electrodes, the optical transmittance is an important parameter, because it directly affects the light output coupling.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, metal oxide nanoparticles synthesized by sol‐gel methods have been used in conjunction with MNWs, mostly for enhanced current collection efficiency when integrated into solar cells. [ 138 ] However, the effect of nanoparticle coatings on improving the chemical and thermal resilience of MNWs have not been investigated thoroughly in many studies. In a work by Zhu et al., [ 139 ] where CuNWs were covered sequentially by ZnO nanoparticles and rGO, it is shown that ZnO nanoparticles alone are not sufficient in preventing the long‐term degradation of CuNWs.…”
Section: Nanowire Coatings To Delay Failurementioning
confidence: 99%
“…The conductivity requirement for the TCO component is in this combination far less stringent than for a stand‐alone TCO. This opens the possibility to build completely functional transparent electrodes with thin TCO layers, which can be rapidly deposited by nonvacuum techniques, such as aerosol‐assisted chemical deposition of a zinc acetate solution or spin‐coating indium tin oxide (ITO) nanoparticle (NP) . Furthermore, this combination benefits from the improved mechanical stability of Ag‐NWs compared with brittle TCOs, which is an important aspect for flexible PVs …”
Section: Introductionmentioning
confidence: 99%